Fikih Moderasi Beragama Dalam Kehidupan Bernegara di Indonesia - Eko Siswanto; Athoillah Islamy (Al-Adalah: Jurnal Hukum dan Politik Islam, 2022)
It is unfortunate that there is a bad stigma by some Muslims who view the mainstreaming of religious moderation in Indonesia as liberalization and secularization of religion in state life. This study intends to identify the values of maqasid shariah in the indicators of religious moderation formulated by the Ministry of Religion of the Republic of Indonesia. This literature research uses a normative-philosophical approach. The analytical theory used is the concept of the maqasid shariah approach developed by Jasser Auda. The results show that there are dimensions of maqasid shariah values in the four indicators of religious moderation in Indonesia. First, the dimension of the value of hifz waton (maintaining the benefit of the state) in the attitude indicator of national commitment. Hifz waton can be a paradigm in an effort to maintain the benefit of state life. Second, the value dimension of hifz 'ird (maintaining the benefit of honor and human dignity) in anti-radicalism indicators. The manifestation of hifz 'ird is in line with various efforts that uphold human values, including the safety of the human soul (hifz nafs). Third, the dimension of the value of the hifz ummah in the indicator of tolerance and accommodative to local culture. The manifestation of the hifz ummah through a tolerance and accommodative attitude towards the diversity of local Indonesian culture will be able to show the universal teachings of Islam, namely rahmatan lil alamin. The theoretical implication of this research is that the indicators of religious moderation in Indonesia are parallel to the universal benefit values that are the orientation of Islamic law (maqasid shariah). The limitation of this research is that it has not studied the form of transformation of religious moderation values in the positivity of Islamic law in Indonesia.